2008
DOI: 10.1590/s1678-77572008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Preload and torque removal evaluation of three different abutment screws for single standing implant restorations

Abstract: Several authors still consider the mechanical problems of fracture and component loosening as the main causes of failure of implant-supported restorations. The purpose of this in vitro study was to compare the preload of three types of screw for transmucosal abutment attachment used in single implant-supported prosthesis through strain gauge and removal torque measurements. Three external hex fixtures were used, and each received a transmucosal abutment (Cera One®), which was fixed to the implant with its resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 5 publications
2
53
0
18
Order By: Relevance
“…Then, in addition to surface roughness, secondary factors such as the material, screw head, and thread design also have to be taken into consideration [5][6][7][8] . Furthermore, several other factors can exert a major influence on screw loosening, such as the structural design of the implant connection, a poor fit with an implant-supported prosthetic crown, and occlusal loading [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Then, in addition to surface roughness, secondary factors such as the material, screw head, and thread design also have to be taken into consideration [5][6][7][8] . Furthermore, several other factors can exert a major influence on screw loosening, such as the structural design of the implant connection, a poor fit with an implant-supported prosthetic crown, and occlusal loading [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the roughness caused by surface treatment increases the friction between the implant surface and bone, influencing primary stability. 9,18,19 Moreover, when the surface treatment increased bone-implant contact, the likelihood of osseointegration increased. 11 However, the high pullout resistance of implants with treated surfaces compared with those having machined surfaces suggests that the surface influences initial stability even when osseointegration does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…17 In these tests, it was observed that the implants with treated surfaces behaved differently than the machined implants. 18,19 This study aimed to evaluate the insertion torque and the pullout resistance of titanium dental implants with treated and untreated surfaces before osseointegration, and to evaluate the effects of these treatments on primary stability.…”
Section: Introductionmentioning
confidence: 99%
“…9 It might lead to a component failure that demanded a more extensive repair. 10,11 There are several factors that can play critical roles in screw joint stability, including the preload and screw geometry. Screw joint preloading, an important mechanical factor in preventing screw loosening, accumulated in the abutment screw as a product of screw tightening.…”
mentioning
confidence: 99%